Barriers of Persons with Physical Disability Over Accessibility and Mobility to Public Buildings in Zambia - Chiluba, Brian Chanda (The Center for Disability Studies and Services Brawijaya University, 2019)
To ensure that there is inclusiveness in the provision of services for PWDs the Zambian government ratified to the UNCRPD by enacting the Zambia PWDs ACT No. 6 of 2012 to precisely look at promoting and protecting the rights of PWDs. Despite this, there has been a lack of implementation of the ACT and specifically about accessibility and mobility of PWDs to public buildings. The aim of this study was to explain barriers to implementation of part five division five of The Zambia PWDs on Accessibility and Mobility to public buildings in Lusaka for PWDs. A qualitative case study approach was utilized with sample of 8 participants who by a method of purposeful and convenient sampling were drawn and using thematic method of analysis. This study found that there is a knowledge gap and reduced general knowledge about the ACT among policy implementers. There is need for awareness among people that own building in Lusaka of the Disability ACT. For the policy makers there is a need for prioritization through national planning, budgeting and various national programs.